Emergence of highly virulent and multidrug-resistant Escherichia coli in breeding sheep with pneumonia, Hainan Province, China - Wang, Mengqi; Li, Xuesong; Guo, Guiying; Rehman, Muhammad Nafees Ur; Gao, Xiaomeng; Fan, Lixia; Yang, Nuo; Zeng, Jifeng; Zheng, Jiping (Frontiers in Microbiology, 2024)
Background: Sheep are a rarely raised livestock in Hainan Island, China, because of the unfavorable tropical marine climate. Here, this article reports a severe pneumonia in the sheep breeding and domestication facility caused acute mortality during the winter 2021-2022. Methods: Six sheep were clinically dissected and histopathologically observed. The bacteria were isolated and cultured by traditional methods and identified by 16S rRNA sequencing. The genotypes, serotypes, virulence genes and antimicrobial resistance genes were analyzed by PCR and whole genome sequencing. The pubMLST website was used for phylogenetic analysis of related strains. Kirby-Bauer disk diffusion method was used for antimicrobial susceptibility test. The antimicrobial susceptibility test standard was referred to the Clinical and Laboratory Standards Institute (CLSI). The virulence of bacteria was detected by mouse infection model. Results: Etiology and histopathology examination of the pneumonia reveled pulmonary abscess and alveolar neutrophilia and pulmonary fibrinous exudates. Escherichia coli was the only bacterial species isolated, primarily from the lungs and blood of the six dead or moribund sheep, a total of 29 E. coli strains were isolated. Antimicrobial resistance profiling shows that all the isolates were resistant to six agents (penicillin, ampicillin, cephalothin, neomycin, erythromycin, and vancomycin) belonging to five classes of antibiotics, classifying them as multi drug resistant (MDR). Furthermore, genotyping analysis revealed all strains were common with 11–17 virulence factors indicating high pathogenicity. The lab mice infection model shows that all strains severely affect the health status particularly weight loss, lethargy, pneumonia and shortly lead to death. The molecular epidemiological analysis indicated most strains share the same genotype as previously reported strains in humans and other farmed animals this suggests a high possibility of Cross-species transmission (CST) of virulent and MDR isolates. This CSC could be from sheep to humans and other farmed animals or from humans and other farmed animals to sheep. Conclusions: Therefore, this study indicates that E. coli is an emerging threat that causes sheep pneumonia in Hainan, and the quarantine of contacts is important to control the spread of virulent E. coli and the transmission of acquired resistance genes between humans and farmed animals such as sheep.